Contemporary Issues in Fasting: Divergent Ramadan Start Dates in Indonesia - Savira, Annida Husna; Nafi'ah, Atikah Zahra; Ulva Tri Amalia; Rahmat, Al Fauzi (NALAR FIQH: Jurnal Hukum Islam, 2024)
The implementation of fasting is often characterized by differences in the initial start time. As happened in Indonesia during the fasting month of Ramadan in 2022. In Islam, there are several sects that give rise to differences. But it must be understood that these differences are not divisions, but diversity. This study will discuss the factors behind the differences in the initial fasting time. With this research, it is hoped that there will be no negative statements in society that corners one party. This research is a research that uses a descriptive qualitative approach. The technique used in this research is critical discourse analysis. The results of this study include understanding, propositions, pillars, conditions, types, wisdom, determining the start of fasting, and the reasons for the difference in the starting time of fasting in Indonesia. Fasting is refraining from something that can break the fast, accompanied by the intention from sunrise to sunset. There are arguments for fasting that come from the Al-Quran and hadith. There are mandatory requirements and valid conditions for fasting and pillars of fasting. The law of fasting can be obligatory, sunnah, makruh, or unlawful. The method used to determine the beginning of fasting is reckoning and rukyat.